"A field open to everybody": Harald Høffding and his classic textbook Outlines of psychology (1882). Issue 3 (3rd July 2019) - Pind, Jörgen L.
Abstract: Psychology was taught at the University of Copenhagen as part of a compulsory first-year course throughout the nineteenth century. In 1883, Harald Høffding (1843–1931) became professor of philosophy at the University having the previous year brought out the first edition of his Outlines of psychology . The book went through numerous editions and received widespread acclaim through translations into a number of languages. It became one of the most widely used textbooks of psychology at the turn of the twentieth century. The book was characterized by its strictly empiricist approach to psychology, by its inclusion of findings from experimental research as well as numerous references to budding research on child development and psychopathology. The book was solidly anchored in classical philosophical approaches to psychology in basing its treatment of psychology on a three-fold division of the psyche into cognition, feeling, and will. Høffding's book showed the influence of both English associationism and of continental European emphasis on the synthetic activity of the self. The book also presented Høffding's original idea on recognition, the so-called "Høffding function." In spite of his eclectic approach to psychology, Høffding himself was particularly enamored of descriptive psychology and critical of the pretensions of experimental psychology to speak for the whole of psychology. In his last psychological work, The great humor from 1916, he endeavored to present a case study illustrating the value and necessity of descriptive psychology.